Sosialisasi Dan Pembekalan Strategi Pemasaran Produk Olahan Pisang Pada Siswa Pondok - Dellia Mila Vernia; Sigit Widiyarto; Dwi Narsih; Mu'thia Mubasyira; Leni Tiwinyanti (LPPM UMRI, 2020)
Marketing strategy is very important in business processes. This process is the final process of a production. Community service activities are carried out in the rice fields of Ciputat sub-district, South Tangerang, West Java. This activity focuses on empowering orphanage students, especially in the provision of effective marketing methods, it is hoped that pondok students have an interest in entrepreneurship. The number of participants was 26 children. The activity will take place from the beginning of December 2019 until March 2020. The implementation method is used with counseling, mentoring and program evaluation. Achieved results: students can independently market products according to target sale, students know the market share, and can use online marketing.